2020
DOI: 10.1016/j.celrep.2020.107952
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Stem Cells Are Radioresistant and Regenerate the Intestine

Abstract: Highlights d Cycling Msi1 + ISCs in the intestinal crypt are DNA damage resistant d Msi1 + ISCs enable fast intestinal repair ahead of Lgr5 high CBCs d Paneth cells preferentially arise from Msi1 + ISCs during homeostasis and repair

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 53 publications
3
40
0
Order By: Relevance
“…Situated just above the last Paneth cell in the crypt are the +4 position cells, which have a unique transcriptional profile including expression of Hopx (Takeda et al, 2011), Tert (Breault et al, 2008;Montgomery et al, 2011), Bmi1 (Sangiorgi and Capecchi, 2008), and Lrig1 (Powell et al, 2012) (Figure 2). These cells have previously been deemed the RSC population, which reconstitutes Lgr5 + CBCs during a state of injury (Breault et al, 2008;Sangiorgi and Capecchi, 2008;Montgomery et al, 2011;Powell et al, 2012), and have been previously shown to be radiation resistant (Tao et al, 2017;Montenegro-Miranda et al, 2020;Sheng et al, 2020), suggesting that these cells can survive acute injury in the crypt and fill in for their damaged counterparts. However, recent literature has underscored the complexity of characterizing these cells and called into question their "stemness."…”
Section: The Role Of +4 Position Cells and Secretory Precursors In Rementioning
confidence: 99%
See 1 more Smart Citation
“…Situated just above the last Paneth cell in the crypt are the +4 position cells, which have a unique transcriptional profile including expression of Hopx (Takeda et al, 2011), Tert (Breault et al, 2008;Montgomery et al, 2011), Bmi1 (Sangiorgi and Capecchi, 2008), and Lrig1 (Powell et al, 2012) (Figure 2). These cells have previously been deemed the RSC population, which reconstitutes Lgr5 + CBCs during a state of injury (Breault et al, 2008;Sangiorgi and Capecchi, 2008;Montgomery et al, 2011;Powell et al, 2012), and have been previously shown to be radiation resistant (Tao et al, 2017;Montenegro-Miranda et al, 2020;Sheng et al, 2020), suggesting that these cells can survive acute injury in the crypt and fill in for their damaged counterparts. However, recent literature has underscored the complexity of characterizing these cells and called into question their "stemness."…”
Section: The Role Of +4 Position Cells and Secretory Precursors In Rementioning
confidence: 99%
“…Msi1 has previously been identified as a marker of ISCs (CBCs, and +4 position cells) (Kayahara et al, 2003;Li et al, 2015). Sheng et al (2020) set out to understand if Msi1 can rapidly cycle to restore a damaged intestinal epithelium. This was investigated by generating an Msi1CreERT2 allele for lineage tracing analysis and this led to the discovery that Msi1 + cells are indeed positioned in the +4 position in the intestinal crypt and are resistant to DNA damage via y-irradiation.…”
Section: Msi1 and Tigar: Boosting The Potential Of Darscsmentioning
confidence: 99%
“…To investigate this possibility, we repeated the experiment and assessed tumor burden and signs of intestinal regeneration at day three after irradiation (Figure 4D) . Although this was an early timepoint for assessment of tumor radiation response, attempts at intestinal regeneration are frequently assessed around this timepoint (Metcalfe et al, 2014; Olcina and Giaccia, 2016; Sheng et al, 2020; Wei et al, 2016). We indeed observed that three days post irradiation the majority of mice showed signs of early regeneration (Supplementary Figure 4) .…”
Section: Resultsmentioning
confidence: 99%
“…We next sought to characterize changes in cellular composition after ALI to assess differentiation and emergence of damageassociated regenerative stem cells (DARSCs), as previously noted in models of acute damage (Breault et al, 2008;Montenegro-Miranda et al, 2020;Montgomery et al, 2011;Murata et al, 2020;Powell et al, 2012;Sangiorgi and Capecchi, 2008;Sheng et al, 2020;Takeda et al, 2011;Tao et al, 2017), including submergence damage (Wang et al, 2019). Compared with day 10 submerged growth, ALI culture caused differentiation of colonoid monolayers, with increased expression of MUC2, SLC26a3 (DRA), and CHGA (Figure 2A).…”
Section: Repeated Submergence Injury Induces Differentiation Of Colon...mentioning
confidence: 95%